Vertical structural variability of diurnal internal tides inside a mesoscale anticyclonic eddy based on single virtual-moored Slocum glider observations - Lim, Gyuchang; Park, JongJin (Frontiers in Marine Science, 2022)
The vertical structural variability of the diurnal internal tide (DIT) with a mode-1 wavelength of 420-km inside a mesoscale baroclinic anticyclonic eddy was examined based on observations by a single virtual-moored (VM) Slocum glider. During the glider observational period from September 10 to 19, 2018, the eddy travelled northward approximately 50-km, allowing the glider to scan a cross-section of 50-km wide and 800-m deep inside the eddy. VM observations showed that DIT experienced a noticeable vertical structural variability near the eddy center. In a range of 30-km horizontally from the eddy center (inner center), DIT’s vertical displacements were significantly intensified in the 400–800-m depth below the eddy. In the range of 30–50-km from the eddy center (outer center), DIT was almost uniformly distributed from the surface to 800-m depth. Owing to the spatiotemporally restricted dataset by the glider, the significance of DIT’s modulation observed inside the eddy can be questionable. As a result of comparing DIT’s vertical structural variability in two domains in terms of APE and horizontal kinetic energy (HKE) using CTDs inside the eddy and ADCPs outside the eddy, DIT’s vertical structure inside the eddy was significantly distinguished from that outside the eddy. The relative vorticity inside the eddy was estimated based on the satellite dataset; it was negatively great in the inner center (approximately 0.35 – 0.25f) and small in the outer center (approximately 0.2 – 0.1f). These observational behaviors indicate a close relationship between them; the vorticity-dependent modulation of the DIT seems to be observationally confirmed inside the eddy. Further, in order to examine the energy transferring behavior in low vertical modes, a wavenumber spectral analysis was performed on the DIT displacements and the lowest four wavenumbers, K_z (1) through K_z (4), showed a similar behavior to those observed in DIT’s vertical structural variability inside of the eddy; the relative power of the sum of K_z (2) K_z (4) with respect to K_z (1) was strong in the inner center and weakened in the outer center. These results seem to support that the wave-eddy interaction is nonuniform inside the eddy and partially depends on the relative vorticity.